Kunstenaars uit de DDR. - Galerie Jan De Maere, Brussel; Casino, Knokke (Brussel : Galerie Jan De Maere, 1984)
Frankenstein, Wolfgang ; Händler, Rolf ; Metzkes, Harald ; Sitte, Willi ; Tübke, Werner ; Womacka, Walter
Kunstenaars uit de DDR, Galerie Jan De Maere, Brussel ; Casino, Knokke, 1984
boek
Keywords: Duitsland; DDR